COMPARATIVE STUDIES OF HEPATITIS C PREVALENCE AMONG PATIENTS ATTENDING SELECTED PUBLIC HEALTH FACILITIES IN KARU L.G.A. NASARAWA STATE, NIGERIA - Eze, Chidiebere Christopher; Ayoade , Biodun Rukayat; Dada, John Oluwasegun; Ciroma , Blessing Godiya (FUDMA JOURNAL OF SCIENCES, 2025)
Hepatitis C Virus (HCV) infection is responsible for a large proportion of hepatitis morbidity and mortality in Nigeria as more than 90% of infected persons are unaware of their conditions and as such do not bother to seek treatment. This study aimed to assess how demographic variables and behavioural practices influence the distribution of HCV infections among patients attending Uke General Hospital and the Primary Health Centre (PHC) in Karu Local Government Area of Nasarawa State, Nigeria. A total of 360 patients were examined, 180 from each healthcare facility, with their blood samples collected and screened using Serological Test and Molecular Assay procedure. A designed questionnaire was administered to each consenting participant during the period of the study for socio demographic data. The data generated were analysed using STATA Version 17.0 at P< 0.05 level of significance. Uke General Hospital recorded slightly more HCV prevalence (13.3%) than PHC Karu (10.0%). Higher HCV prevalence was reported among patients aged 30–39 in both health facilities with males showing a significantly greater level of infection compared to females. Additionally, individuals with little or no formal education recorded more infections. Behavioural factors such as tattooing, scarification, having multiple sexual partners, and history of blood transfusion were identified as significant risk contributors. High prevalence of HCV in Karu LGA remains a significant public health concern, particularly among young adults, men, and patients with low educational attainment. Addressing this issue requires a multi-dimensional approach focused on education, behavioural change, access to healthcare, and policy regulation.